X-2x+2+3x=

Simple and best practice solution for X-2x+2+3x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-2x+2+3x= equation:


Simplifying
X + -2x + 2 + 3x = 0

Reorder the terms:
2 + X + -2x + 3x = 0

Combine like terms: -2x + 3x = 1x
2 + X + 1x = 0

Solving
2 + X + 1x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + X + -2 + 1x = 0 + -2

Reorder the terms:
2 + -2 + X + 1x = 0 + -2

Combine like terms: 2 + -2 = 0
0 + X + 1x = 0 + -2
X + 1x = 0 + -2

Combine like terms: 0 + -2 = -2
X + 1x = -2

Add '-1x' to each side of the equation.
X + 1x + -1x = -2 + -1x

Combine like terms: 1x + -1x = 0
X + 0 = -2 + -1x
X = -2 + -1x

Simplifying
X = -2 + -1x

See similar equations:

| (4y+1)(5y+7)= | | 2x=32 | | -6(x-6)=36 | | senx+1=cosx | | -5(x-3)+2x= | | 3/4=b/32 | | 5x+-3=2(3+x) | | 4/8+2= | | 4(a-6)=4a-10 | | f(-27.018)=31.572x-17.741 | | 4a-(a-5)=23 | | f(6.2)=31.572x-17.741 | | 6z+24=6(2+4) | | -b*-1=-3m+1 | | 8-7x-5-7x=5 | | (2x^2-2x-4)+(-4x^2+5x-1)= | | 5(x-2)-4(3x+3)=4x-11 | | b-15=24 | | -3(x+3)=6x+63 | | 0.02+0.7=0.8 | | (2x^2-4x-6)+(-5x^2-6x-3)= | | 81=1.25+3.25 | | 7x+5x=550 | | 3x-50=2 | | b/4-5=6 | | 3x-3=50 | | 3tan^2x+10tanx-25=0 | | (2b-12)+b=33 | | 2l+o=-4 | | 9c-1=c-25 | | -0.06x^2-0.6x+6=p | | 16x+4=10+15x |

Equations solver categories